A critical evaluation on the effectiveness of ISO 9001:2000 (QMS) implementation in Malaysian and Saudi manufacturing companies - Al-Turki, Abdullah Nasser; Faris, Waleed Fekry (Inderscience Publishers, 2010)
Saudi Arabia is encouraging private sector growth to lessen the kingdom’s dependence on oil. As part of its effort to attract foreign investment and expand the economy, Saudi Arabia acceded to the World Trade Organization (WTO) in 2005 after many years of negotiations. There are some 3,657 factories currently operating in the Saudi Arabia with total investments of SR 256 billion ($68 billion) involved. International consumers and customers alike are looking for the ISO 9001:2000 certifications for their purchases. For many, the certification is synonymous to quality and as such the ISO 9001:2000 certification is almost mandatory for manufacturing companies, which want to export their products. On the other hand, Kingdom of Saudi Arabia looks at Malaysia as a model country for manufacturing success. For this reason, this paper is studying the effect of ISO 9001:2000 among these two countries. ISO 9000 have been a widely applied quality standards for many industrial sectors. The purpose of this study is to evaluate the implementation and certification of ISO 9000 and its impact on key performance issues in industrial sector in both Malaysia and Saudi Arabia.